Acute gastric volvulus secondary to eventration of the diaphragm in a child - Singal A; Vignesh K; Matthai J (Wolters Kluwer Medknow Publications, 2006)
We report an 18-month-old boy who presented with acute organoaxial volvulus of stomach secondary to eventration of diaphragm. Clinically, the child exhibited classical triad of epigastric distension, unproductive retching and inability to pass a nasogastric tube. Successful operative management is presented and relevant literature is discussed.